SPERM FACTORS AND EGG ACTIVATION: Divergent sperm factors for egg activation in amphibian fertilization. Issue 1 (23rd May 2022) - Iwao, Yasuhiro; Ueno, Shuichi
Abstract : Mature amphibian eggs arrested at meiotic metaphase II must undergo activation to initiate embryonic development soon after fertilization. Fertilizing sperm provide eggs with a signal that induces egg activation, and an increase in intracellular Ca 2+ concentration in the egg cytoplasm (a Ca 2+ rise) is the most important signal for this initiation. The sperm transmits the signal for the Ca 2+ rise, known as the sperm factor, which is divergent between anurans and urodeles. In monospermic anurans, the sperm transmits the signal through a receptor on the egg membrane, causing a single rapid Ca 2+ rise. Sperm matrix metalloproteinase-2 is a potential candidate for the receptor-mediated sperm factor in anurans. In physiologically polyspermic urodeles, multiple slower Ca 2+ rises are caused by a soluble sperm factor (sperm-specific citrate synthase) which is transferred to the egg cytoplasm after sperm–egg fusion. We discuss the molecular mechanisms of egg activation in amphibian fertilization, focusing on recent progress in characterizing these sperm factors and their divergence during the evolution of tetrapod vertebrates.